Communicative Approach in Language Teaching: a Method to Improve Students’ Interpersonal Skills - Ana Elvia Jakfar; Irfan Dwi Yulianto (International Conference on Education and Language (ICEL), 2013)
AbstractCommunicative approach has become a popular method used in teaching and learning a language. This method has also been widely used in Indonesia for teaching and learning English. The basic assumption used by this method is that language is a means of communication, so that when learning a language the learners also need to engage in meaningful communicative activity. Thus, typical classroom activities involved many interactions among the language learners and the teachers, for example, role playing, information gap activities, and games. Consequently, for the success of the classroom activity, the students not only need to be taught the language skills needed but also the interpersonal skills. Interpersonal skills defines as the ability to interact effectively with someone and teamwork. Furthermore, interpersonal skills such as leveraging diversity, empathy, leadership, influence, communication, conflict management, and synergy are soft skills that students need to master, especially since Indonesia Education system decided to include soft skills in the curriculum. It means that teacher needs to use teaching methods that can develop students’ hard skills and soft skills.This presentation aims at reporting a research result that investigated the use of communicative approach to teach both language skills and interpersonal skills of the students. A literature review on the communicative approach teaching method and the importance of interpersonal skills for successful communication will be reviewed. Finally, the presentation will discuss about the practical recommendations on how to use the approach, so that it can develop both the language skills and the interpersonal skills of the students.